2013
DOI: 10.1245/s10434-013-3013-7
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Imatinib in Locally Advanced Gastrointestinal Stromal Tumors (GIST): The EORTC STBSG Experience

Abstract: Our analysis comprising the largest group of GIST patients treated with neoadjuvant imatinib in routine practice indicates excellent long-term results of combined therapy in locally advanced GISTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
147
1
23

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(181 citation statements)
references
References 36 publications
4
147
1
23
Order By: Relevance
“…This is markedly better than the 18-24 months seen with advanced GIST as a whole cohort in various studies, but in line with what has been seen in the BRF 14 study (PFS: 39.4 months) (17,22). The operable cancers (including locally advanced) had a median EFS of 58 months ( 5 year EFS: 50%), which is lower than published data (14,21) for operated and locally advanced cancers. The differences can be attributed to the small sample size, short follow-up and real world nature of the data compared to trial data.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is markedly better than the 18-24 months seen with advanced GIST as a whole cohort in various studies, but in line with what has been seen in the BRF 14 study (PFS: 39.4 months) (17,22). The operable cancers (including locally advanced) had a median EFS of 58 months ( 5 year EFS: 50%), which is lower than published data (14,21) for operated and locally advanced cancers. The differences can be attributed to the small sample size, short follow-up and real world nature of the data compared to trial data.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, recommendations for the adjuvant and neoadjuvant treatment of operated GIST rely on the various classifications predicting recurrence, based on size, site and mitotic index, without taking into account tumor genotype (6,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The median OS of patients treated with both dose levels was 3.9 years, while the median PFS was 1.7 (400 mg dose level) and 2 years (800 mg dose level), respectively. While the PFS is similar to the updated SWOG data (19 months), more recently published data, albeit with smaller numbers, from other groups have documented increased PFS with first line imatinib, ranging from 34-43 months (4)(5)(6). Within the confines of smaller numbers and non-prospective data collection, these differences can be explained by upfront treatment with imatinib in the current era (as opposed to the prior use of ineffective chemotherapy and radiotherapy in the EORTC-STBSG/AIGTG study) as well as reducing tumor size at diagnosis across time-periods.…”
supporting
confidence: 71%
“…also may have lesser relevance in current practice as well trials, considering the early diagnosis of GIST nowadays, the routine use of adjuvant imatinib in high risk GIST as well as reducing tumor size at diagnosis in patients with newly diagnosed GIST. The additional use of neoadjuvant imatinib in patients who are initially presenting with unresectable disease may further reduce the relevance of tumor size as a predictor of outcomes (5,18). Answers to long-term survivorship in GIST, as in other tumors, are likely to be identified by assays using next generation sequencing on large scale, rather than purely clinical factors.…”
Section: Editorialmentioning
confidence: 99%
“…A clinical trial with a large sample size demonstrated a median time Zhan-De He 1 , Xin-En Huang 2 , Jian-Nong Zhou 3 * to progression of 24 months and a median overall survival time of 57 months focusing on treatment with imatinib for patients with unresectable or metastatic GIST . Furthermore, recent reports suggested that preoperative imatinib use can increase the resectability rate and reduce procedure-related mortality, thereby improving the survival of GIST patients (Rutkowski et al, 2013;Wang et al, 2013). But it is not clear in China, what kind of combination of treatment, especially, with imatinib could be recommended.…”
Section: Introductionmentioning
confidence: 99%